PAS perintah Malaysia : salam Tok Guru - Mohd. Sayuti Omar, 1960- (Kuala Lumpur, Malaysia : Tinta Merah, 1999)
Politics in Malaysia and the Parti Islam Semalaysia, an Islamic political party in Malaysia.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Parti Islam SeMalaysia; Malaysia -- Politics and government